Armenian-Georgian Relations in the Post-Soviet Era: Challenges and Opportunities - Babajanyan, Mane (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
As two South Caucasian neighboring countries, Armenia and Georgia share cultural and religious proximity, but there are several contradictions between them caused by both external and internal factors. This study attempts to shed light on the existing controversies and unresolved issues between Armenia and Georgia that pose a challenge for the former.
Keywords: International relations